FORMULASI DAN KARAKTERISASI NANOSTRUCTURED LIPID CARRIER (NLC) TABIR SURYA ETHYLHEXYL TRIAZONE - Permata Syamsun, Firuzia
Exposure to UV rays from the sun on the skin can cause various negative effects, such as redness and wrinkles on the skin, immunosuppression, and can even cause skin cancer. The formulation of sunscreen into the NLC is reported can reduce the number of sunscreen applications used during sun exposure by increasing the SPF. This study aimed to develop, characterize, and evaluate an NLC formulation containing Ethylhexyl Triazone (EHT). The determination of the NLC formula was carried out through three optimization stages, namely optimization of liquid lipids, optimization of the ratio of solid lipids and liquid lipids, and optimization of surfactant concentrations. Process optimization was also carried out by comparing the two types of sonicators used in the manufacture of NLC. Then the characterization was carried out in the form of measuring particle size, polydispersity index (PDI), zeta potential, percentage of entrapment efficiency, and determining the value of sun protection factor (SPF). NLC stability test was carried out at 40oC/75% RH for 14 days. The final formula for NLC EHT based on optimization results is EHT 1% (w/v), tween 80 4% (w/v), 2% cetyl alcohol (w/v), olive oil 4% (w/v), and aquadest ad up to 100%. The NLC with the final formula was made using a probe-type sonicator and had a particle size of 135,50 ± 4,45 nm, polydispersity index 0,33 ± 0,01, zeta potential -33,86 ± 4,44 mV, and entrapment efficiency of 99.93 ± 0.05%. The SPF for NLC-EHT is 32.43 ± 1.50 (High SPF), higher than the SPF of EHT made as a regular emulsion preparation (28.41 ± 0.40). During 14 days of storage to test, there was a significant change in the NLC particle size. However, the value of PDI, percentage of entrapment efficiency, and SPF did not change significantly. Thus, the developed NLC-EHT formulation provides a useful alternative to sunscreen formulations.